Cohabiting the Territory: Responsible Tourism as a Practice of Hospitality and Community Care - Musarò, Pierluigi; Cappi, Valentina; Vignola, Marta (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
The study of tourism is one of the privileged gateways for understanding the territory, not only from an economic point of view. Tourism plays an essential role in the social and spatial dialectic that assigns meaning to places: on the one hand, it feeds the individual and collective imaginary through the production of icons and representations; on the other hand, it shapes places, which become "touristy" through visible transformations that spatialize those same images. Since the 1970s, various observers have denounced the tourist phenomenon as a new form of alienation, environmental destruction or imperialism. In the wake of these and other calls for the need to rethink and govern an ever-growing industry, the so-called responsible tourism has emerged as a mode of travel that meets and respects the needs of travelers and host regions while protecting and enhancing the opportunities of specific territories. Starting from a reflection on the dimensions, impacts and changes taking place in one of the phenomena characterizing contemporary times, this article, as well as the special issue it introduces, takes as a case study IT.A.CÀ_migrants and travelers, the first festival at the European level focused explicitly on the theme of responsible tourism. The journey through the different editions of IT.A.CÀ_migrants and travelers allows us to assess assumptions, outcomes and future potential of experiences and practices that in recent years, through participatory processes of sharing, co-designing, dialogue and experimentation, have sought to combine the sustainability of tourism with the well-being of citizens, imagining a valorization of the territory that promotes the transition to a sustainable cohabitation of the Earth.